Silencing STAT3 with short hairpin RNA enhances radiosensitivity of human laryngeal squamous cell carcinoma xenografts in vivo - LI, XIAOMING (D.A. Spandidos, 2010)
Short hairpin RNA (shRNA) targeting signal transducer and activator of transcription 3 (STAT3) potentiate the radiosensitivity of human laryngeal squamous carcinoma cells in vitro. In the present study, we investigated the inhibitory effect of STAT3 shRNA plus radiotherapy on nude mouse laryngeal squamous cell carcinoma xenografts. The xenotransplanted tumors were treated with STAT3 shRNA, with or without radiation, following a planned scheme. The inhibition rate for tumor growth was calculated and the tumor growth curve was plotted. In addition, the expression of p-STAT3, B cell lymphoma 2 (Bcl-2), p53, vascular endothelial growth factor (VEGF) protein and intratumoral microvessel density (MVD) was determined by immunohistochemistry. Flow cytometry was used to detect the rate of cell apoptosis. The results revealed that STAT3 shRNA transfection plus radiotherapy significantly minimized tumor volume and increased the rate of tumor inhibition. p-STAT3 protein expression and intratumoral MVD were observed to be down-regulated, whereas apoptosis was increased. There was a positive correlation between the expression of p-STAT3 and Bcl-2, and also between the expression of p53 and VEGF, and MVD. These findings indicate that STAT3 shRNA potentiate the radiosensitivity of laryngeal carcinoma xenografts in vivo by regulating downstream signaling proteins in the STAT3 pathway.